Root colonization by the endophytic fungus Piriformospora indica shortens the juvenile phase of Piper nigrum L. by fine tuning the floral promotion pathways - Lekshmi, R. S.; Sora, S.; Anith, K. N.; Soniya, E. V. (Frontiers in Plant Science, 2022)
Piriformospora indica, the mutualistic biotrophic root colonizing endosymbiotic fungus belonging to the order Sebacinales, offers host plants various benefits and enhances its growth and performance. The effect of colonization of P. indica in Piper nigrum L. cv. Panniyur1 on growth advantages, floral induction and evocation was investigated. Growth and yield benefits are credited to the alteration in the phytohormone levels fine-tuned by plants in response to the fungal colonization and perpetuation. The remarkable upregulation in the phytohormone levels, as estimated by LC- MS/MS and quantified by qRT-PCR, revealed the effectual contribution by the endophyte. qRT-PCR results revealed a significant shift in the expression of putative flowering regulatory genes in the photoperiod induction pathway (FLOWERING LOCUS T, LEAFY, APETALA1, AGAMOUS, SUPPRESSOR OF CONSTANS 1, GIGANTEA, PHYTOCHROMEA, and CRYPTOCHROME1) gibberellin biosynthetic pathway genes (GIBBERELLIN 20-OXIDASE2, GIBBERELLIN 2-OXIDASE, DELLA PROTEIN REPRESSOR OF GA1-3 1) autonomous (FLOWERING LOCUS C, FLOWERING LOCUS VE, FLOWERING LOCUS CA), and age pathway (SQUAMOSA PROMOTER LIKE9, APETALA2). The endophytic colonization had no effect on vernalization (FLOWERING LOCUS C) or biotic stress pathways (SALICYLIC ACID INDUCTION DEFICIENT 2, WRKY family transcription factor 22). The data suggest that P. nigrum responds positively to P. indica colonization, affecting preponement in floral induction as well as evocation, and thereby shortening the juvenile phase of the crop.